A Pioneer of Italian Sports Pedagogy and Philosophy - Isidori Emanuele; Kosiewicz Jerzy (Sciendo, 2017)
The biography we present here in this issue of our journal refers to the story of Italian scholar, educationist, and philosopher, Emanuele Isidori, Vice-Rector for International Relations and Cooperation and head of the Laboratory of General and Sport Pedagogy of the Foro Italico University of Rome in Italy. The biography of Emanuele tells us the story of a pioneer both in sports pedagogy and sports philosophy in his home country of Italy, where the idealist tradition and some prejudices regarding sport and its science seem to have hindered the development process of the two subjects for many years. What emerges from this story is the commitment and strenuous effort of the scholar to develop sports humanities in his country and to help his university and other Italian researchers interested in the scholarly field develop their knowledge through collaboration with the most prestigious European institutions devoted to the study of sport and physical activity.